Automatic Detection of Meniscal Area in the Knee MR Images - Saygili, Ahmet; Kaya, Heysem; Albayrak, Songul (IEEE, 2016)
Nowadays computer-aided medical systems has become widespread. These systems assist the scientists in the medical field with diagnosis and treatment. In the same vein, in this study detection of medial meniscus from MR images of the knee is performed automatically. Knee MR images used in this study were obtained from Osteoarthritis initiative. 75% of MR images were used for training, while the remainder was used for the test. Attributes to be used in the training and test process were obtained by the Histogram of Oriented Gradients (HOG) method. The regression approach used in the training process and found correlation and mean square error value for patch in different sizes. The maximum correlation value detected is about 91%. The objective of the study will be to accelerate the current system for minimizing the time for treatment in the later stages and to provide a functional decision support system.
Keywords: Knee MR; HOG; medical image processing; SEGMENTATION; TEARS; Engineering